Numerical analysis of soil-steel bridge - Bęben, Damian; Wrzeciono, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents a numerical analysis of the soil-steel bridge in the scope of static loads. The Abaqus program based on the FEM was used to calculations. Maximum displacements were obtained in the shell crown, and the largest stresses in the haunches. Calculation results were compared with the experimental ones and previous calculations obtained from the Robot Millenium program. The shapes of calculated displacements and stresses are similar to those obtained with the experiment, but the absolute values were generally higher than measured ones. Using both calculation programs, the relative reductions of displacement were in the range of 15–39%, and 17–44% for stresses in favour of the Abaqus program. Developed calculation model of the soil-steel bridge in the Abaqus program allows to obtain reasonable values of internal forces in the shell structure.